IMPLIKASI AL-WAQF WA AL-IBTIDA’ DALAM PENAFSIRAN : STUDI ANALISIS PEMIKIRAN AHMAD BIN MUHAMMAD AL-ASYMUNI DALAM QS. AL-BAQARAH - Sukirno; Ahmad Hawasi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the crucial role of al-waqf wa al-ibtida’ in preserving accurate Qur’anic interpretation, since decisions about where to pause and resume recitation directly affect tafsir, i‘rab, and qirā’āt. The research aims to analyze Ahmad ibn Muhammad al-Asymuni’s concept of al-waqf wa al-ibtida’ in Manar al-Huda and to explore its implications in Surah Al-Baqarah. Employing a qualitative approach, this study applies library research and content analysis to primary and supporting sources. The findings reveal that classifications such as al-tam, al-kafi, al-hasan, and al-jaiz generate significant variations in grammatical construction, legal interpretation, and recitational modes. The study concludes that mastery of al-waqf wa al-ibtida’ constitutes an essential methodological tool in Qur’anic exegesis, as it safeguards semantic precision and prevents misinterpretation.